Efektivitas Pemanfaatan Komunitas Virtual Facebook Sebagai Media Promosi Produk Kuliner Pada Masa Pandemi Covid-19 - Latuhihin, Salfia; Sfenrianto (Fakultas Ekonomi Universitas Gresik, 2023)
Todays, technological developments are developing rapidly and indirectly affecting business activities, especially during Covid-19 pandemic, resulting in many people choose to doing something as online. This study aims to see the effect of the Use of Facebook Virtual Community as promotion media of culinary products during the Covid-19 pandemic, used a quantitative research method and the AIDA concept analysis. Sources of data in this study are members of two groups Facebook that specifically sells culinary products that consists of 7,700 populations with using Slovin method. The results said that the used of the Facebook virtual community as a promotional media is declared